Three- dimensional simulation in the scalar function using the simplex element (ADVANCED TECHNOLOGIES AND COMPUTER SCIENCE, 2021)
The finite element method is a numerical method for solving differential equations encountered in physics and technology. The emergence of this method is associated with the solution of space research problems. It was first published in the work of Turner, Cluj, Martin and Topp. This work contributed to the emergence of other works; a number of articles were published with examples of the finite element method to the problems of structural mechanics of continuous media.The main idea of ​​the finite element method is that any continuous quantity, such as temperature, pressure and displacement, can be approximated by a discrete model, which is built on a set of piece-continuous functions defined on a finite number of subdomains.The finite element method has evolved from a numerical procedure for solving problems in structural mechanics into a general method for numerically solving a differential equation or a system of differential equations. This progress has been made over a fifteen-year period through the development of high-speed, digital computing machines needed for more accurate calculations of aircraft structures, as well as through "the assistance of the National Committee for Space Research. The computing machine has accelerated many complex numerical calculations. space required the allocation of funds for fundamental research and stimulated the improvement of universal computing programs.The finite element method is used in the design of aircraft, rockets, various spatial shells.